Kinetic characterization of a novel acid ectophosphatase from Enterobacter asburiae - Sato, Vanessa Sayuri; Galdiano Júnior, Renato F.; Rodrigues, Gisele Regina; Lemos, Eliana G. M.; Junior, João Martins Pizauro (The Microbiological Society of Korea, 2016)
Expression of acid ectophosphatase by Enterobacter asburiae, isolated from Cattleya walkeriana (Orchidaceae) roots and identified by the 16S rRNA gene sequencing analysis, was strictly regulated by phosphorus ions, with its optimal activity being observed at an inorganic phosphate concentration of 7 mM. At the optimum pH 3.5, intact cells released p-nitrophenol at a rate of 350.76 ± 13.53 nmol of p-nitrophenolate (pNP)/min/108 cells. The membrane-bound enzyme was obtained by centrifugation at 100,000 × g for 1 h at 4°C. p-Nitrophenylphosphate (pNPP) hydrolysis by the enzyme follows “Michaelis-Menten” kinetics with V = 61.2 U/mg and K0.5 = 60 μM, while ATP hydrolysis showed V = 19.7 U/mg, K0.5 = 110 μM, and nH = 1.6 and pyrophosphate hydrolysis showed V = 29.7 U/mg, K0.5 = 84 μM, and nH = 2.3. Arsenate and phosphate were competitive inhibitors with Ki = 0.6 mM and Ki = 1.8 mM, respectively. p-Nitrophenyl phosphatase (pNPPase) activity was inhibited by vanadate, while p-hydroxymercuribenzoate, EDTA, calcium, copper, and cobalt had no inhibitory effects. Magnesium ions were stimulatory (K0.5 = 2.2 mM and nH = 0.5). Production of an acid ectophosphatase can be a mechanism for the solubilization of mineral phosphates by microorganisms such as Enterobacter asburiae that are versatile in the solubilization of insoluble minerals, which, in turn, increases the availability of nutrients for plants, particularly in soils that are poor in phosphorus.
Keywords: acid ectophosphatase; ATPase; Enterobacter asburiae; inhibition; p-nitrophenylphosphate; pyrophosphatase